Narrow-band filter for satellite communication systems - Alexander Vladimirovich Strizhachenko; Sergey Nikolayevich Shulga (Institute of Advanced Engineering and Science, 2021)
Design narrow-band compact filters, based on high-quality waveguide-dielectric resonators with anisotropic materials is the subject of this paper. Filter represents a segment of a rectangular waveguide rotated around the longitudinal axis of the waveguide 90 degrees and containing one or more dielectric inserts that completely fill the resonator along the narrow wall of the waveguide and partially along the wide one. A distinctive feature of the proposed filter is higher slope steepness of the amplitude-frequency characteristic, and high manufacturability in the centimeter range. The designed narrow-band filter satisfies contradictory requirements: it combines narrow bandwidth (≈ 0.1% of center frequency f0) with low passband insertion loss (≤ 1 dB).